Examining Economic Barriers and Challenges to the Adoption of Renewable Energy in Emerging Markets (Case Study: Solar Panels) - Ghaderi, Zana (Digital Transformation and Administration Innovation, 2023)
In recent years, renewable energy has emerged as an effective solution to the energy crisis, reducing dependence on fossil fuels and mitigating climate change. Among renewable energy technologies, solar panels have gained particular importance due to their versatility in installation scales, low operational costs, and environmental compatibility. However, in many developing countries, the process of adopting and expanding these technologies faces numerous economic challenges. This article, focusing on emerging markets and employing a descriptive-analytical method, examines the economic barriers influencing the adoption of solar panels. The primary identified barriers include high initial costs, lack of supportive and incentive-based systems, limited access to financial resources, and inadequate infrastructure. Moreover, by analyzing case studies in South Asian and African countries, the paper proposes solutions such as targeted policymaking, government financial support, establishment of specialized institutions, and public awareness campaigns to facilitate the adoption of these technologies. The findings of this study may serve as a foundation for decision-making by policymakers, investors, and energy sector stakeholders in pursuing sustainable development.